Secure Video watermarking Algorithm Using K-harris feature point detection with dual watermarks (International Journal of Engineering and Computer Science, 2015)
Now days, cyberspace and compression technology allow the well-known use of multimedia applications. Digital watermarking technique is a process of embedding an unperceptive signature or a copyright message such as an image or signature into a video. The advantages of watermarking are due to its imperceptibility and robustness. This paper proposes a best technique for content-based watermarking based on feature points of a video. At each feature point, the watermark is embedded after scale normalization according to the local characteristic scale. Characteristic scale is the highest scale of the scale-space representation of an image at the feature point. Dual Watermarks increases the robustness of the Watermarked Video. The experimental results show that the presented scheme guarantees high peak signal to noise ratio (PSNR), low mean square error value(MSE), low Bit Error Rate (BER).